For King, Constitution, and Country : The English Loyalists and the French Revolution - Dozier, Robert R., 1932- (Book collections on Project MUSE., 1983)
England trembled in 1792. In May, George III issued a proclamation warning his subjects of ""diverse wicked and seditious writings"" then being circulated which might ""excite tumult and disorder."" The response to this proclamation -- an unprecedented expression of loyalty to crown and constitution -- marked the beginnings of a movement that was to influence British political life well into the nineteenth century. For King, Constitution, and Country is the first full-scale exploration of the nature and origins of this loyalist movement. The British government had genuine cause for concern.